À sombra do Colosso da Lagoa : uma história de futebol em Erechim - Breitkreitz, Luciano Anderson (2013)
In the late 1960s the city Erechim in the state of Rio Grande do Sul, has seen the emergence of a great work iron and concrete dedicated to soccer. The Colosso da Lagoa Stadium still draws attention by its size, and brings to the discussion a question: "What motivated the construction of this stadium?". This paper discusses the fascination that soccer plays in society and believes that the biggest driving force in the world of soccer is the rivalry. The research begins with some general considerations about soccer, his appearance, the expansion of the sport and his arrival in Brazil. Discusses the significance of a stadium for the club and its fans, in addition to physical work. And as the conflict sports, where a soccer match, is reflected in the behavior of a given community. In a second step analyzes the soccer Erechim. As European immigrants were organized for sports and the first records of soccer the city. The birth of Ypiranga FC and the context in which it took the creation of the club, and how the rivalry soccer boosted the construction site of the Colosso da Lagoa Stadium. There's even an assessment about the creation of the Colosso da Lagoa Stadium, the events needed for this large and local mobilization for its implementation. The study also relates the influence of the conquest of the 1970 World Cup for Brazil with marketing action developed by the leaders of Ypiranga partners to raise and increase income equity club. The development of the research was done through literature sources, documentary research in historical archives and private archives, queries to the archives of newspapers and magazines. Was also conducted interviews with club officials and sportswriters at the time of the media sympathetic to the issue